BRAC Approach to Tackling Ultra Poverty: Experiences from Around the World. - Chowdhury, Ahmed Mushtaque. (Tufts University. Tisch Library., 2016)
BRAC works in over 10 countries to tackle ultra-poverty by promoting economic development and social protection, expanding horizons, empowering communities, and promoting well-being and resilience.; Nutrition School: NIL Symposium Presentations, 2016.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy